(untitled) (Swiss Medical Weekly, 2020)
BACKGROUND To address low-value interventions in healthcare, “Choosing Wisely” campaigns provide recommendations of interventions to avoid (RIAs). These are usually developed by expert panels rather than general practitioners (GPs). The aim of our study was to develop RIAs for ambulatory general medicine based on the suggestions of GPs, with their involvement from the very beginning. METHODS This was a nationwide online Delphi survey among Swiss Society of General Internal Medicine members. In round one, each participant suggested two interventions perceived as particularly inappropriate. In round two, the 16 most frequent RIAs were rated by importance on a 0–100 scale and compared with “Choosing Wisely” lists. We calculated descriptive statistics for suggestions and importance ratings, and used regression models to search for associations with GP characteristics. RESULTS Response rates were 7.4% (538/7318) for round one and 18.2% (1357/7468) for round two. GPs provided 1074 suggestions. Out of the 16 most frequent RIAs, 13 corresponded to existing “Choosing Wisely” lists. The RIAs rated most important were: antibiotics in viral infections, unnecessarily duplicated tests and imaging in unspecific low back pain (means 88.5–91.7, standard deviations 18.6–19.9). None of the GPs’ characteristics were associated with any of the five highest rated RIAs except for working in a hospital setting. CONCLUSION Most RIA suggestions from GPs were concordant with previously published recommendations of interventions to avoid, independently of GPs knowledge of these and reflecting their high clinical relevance. In addition, our study revealed some more relevant topics and may help to develop future “Choosing Wisely” recommendations, with the final goal to reduce low-value care.